Study of the electrical properties of nanomatellite polymers (for low-density polyethylene LDPE ZnO) (JOURNAL OF UNIVERSITY OF BABYLON for Pure and Applied Sciences, 2018)
Some electrical properties have been studied of polymer nanocomposites films prepared by pressure technique. This study includes some ( D.C & A.C) electrical test for (LDPE-ZnO) polymer  nanocomposities  with different concentration as (0,10,20,30,40,45 and 50) wt.% of  (ZnO) .The FT-IR measurements refer to that no change on chemical structures except some minor variations. XRD of polymers films without additive have no peaks (amorphous structure) but after adding nanomaterial the peaks are appearing. D.C. conductivity of the nanocomposites have been increased  with increasing temperature at different concentrations of (ZnO) nanoparticles. The activation energy decreases with increasing the concentrations of the nanoparticles additives. The A.C electrical properties show that the dielectric constant and dielectric loss decrease with increasing the frequency of applied electrical field and they increase with increasing of the concentration of nanoparticles.